2019
DOI: 10.1016/j.schres.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

A multi-dimensional approach to the relationship between insight and aggressiveness in schizophrenia: Findings from the FACE-SZ cohort

Abstract: Our study confirms that a multi-dimensional approach to insight and aggressiveness is essential to understand the types of links between these clinical states. Insight may trigger the expression of an underlying hostile tendency, maybe via depression and self-stigmatisation. This should be taken into account in therapeutic approaches to improve insight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…The inconsistencies in the above conclusions may be related to regional and cultural differences, selection of included cases, and sample size. 11,41 This study showed that the total PANSS, positive factors, general pathological factors, and disease severity scores were all higher in the aggressive group than in the non-aggressive group, which is similar to the result of research by van Dongen JD et al 42 Meanwhile, this study found that the group with aggressive behavior had better insight, which was contrary to the results of Witt et al, 15 who found that violence is closely related to a lack of insight. However, our results were supported by Schandrin et al study, 41 which speculated that insight may trigger the expression of an underlying hostile tendency, possibly via depression and self-stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistencies in the above conclusions may be related to regional and cultural differences, selection of included cases, and sample size. 11,41 This study showed that the total PANSS, positive factors, general pathological factors, and disease severity scores were all higher in the aggressive group than in the non-aggressive group, which is similar to the result of research by van Dongen JD et al 42 Meanwhile, this study found that the group with aggressive behavior had better insight, which was contrary to the results of Witt et al, 15 who found that violence is closely related to a lack of insight. However, our results were supported by Schandrin et al study, 41 which speculated that insight may trigger the expression of an underlying hostile tendency, possibly via depression and self-stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies in the above conclusions may be related to regional and cultural differences, selection of included cases, and sample size. 11 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this relationship may depend on a number of clinical, contextual, and cultural factors, such as socioeconomic status, engagement with mental health services, stigmatization, and severity of the illness [1,6,12,13]. Moreover, several potential confounders can be identified, for example, negative and positive symptoms [14], hostility [15], cognitive abilities [16,17], levels of social cognition [18], and extrapyramidal side effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin sind konflikthafte Eskalationen im Stationsalltag und disziplinarische Entlassungen keine Seltenheit. Dies führt bei Patienten mit aggressiver Symptomatik zu einem hohen Leidensdruck und beim Bewusstwerden der eigenen Verhaltensweisen zu Selbststigmatisierung (Schandrin et al 2019). Diese restriktiven Formen sind keine nachhaltigen Methoden, um die dysfunktionalen Verhaltensweisen langfristig zu bessern.…”
Section: Hintergrund Und Aktuelle Situationunclassified